1989
DOI: 10.1017/s0954579400000511
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of causes for delinquency and criminality: Lifespan perspectives

Abstract: This review of family, twin, and adoption studies on offender behaviors points to the importance of a genetic predisposition as a partial explanation for criminality in some populations. Twin and adoption studies show that criminality increases with the presence of criminality in biological relatives; the environmental effects of having a criminal adoptive parent also increase the risk of adoptee criminality. Delinquency is described developmentally as a fairly typical phase for many adolescents. Because of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
102
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(114 citation statements)
references
References 26 publications
11
102
1
Order By: Relevance
“…Serious types of violent behavior in adulthood may have different etiologies than violent behaviors in adolescence [2,30], and thus we wanted to keep the behavioral outcomes as homogenous as possible in terms of their underlying causes. Moreover, given that the data were drawn from a nationally representative sample, the incidence of physical fighting (particularly with injuries) was relatively rare in adulthood, making it difficult to analyze fighting ability in adulthood.…”
Section: Methods Datamentioning
confidence: 99%
“…Serious types of violent behavior in adulthood may have different etiologies than violent behaviors in adolescence [2,30], and thus we wanted to keep the behavioral outcomes as homogenous as possible in terms of their underlying causes. Moreover, given that the data were drawn from a nationally representative sample, the incidence of physical fighting (particularly with injuries) was relatively rare in adulthood, making it difficult to analyze fighting ability in adulthood.…”
Section: Methods Datamentioning
confidence: 99%
“…It is not that the risk factors are different in type from those associated with life-course-persistent antisocial behavior, but rather that they are much more weakly associated. The one exception concerns membership of a deviant peer group (DiLalla & Gottesman, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Whereas some studies have found evidence for substantial genetic influences in the development of childhood antisocial behavior problems (Eaves et al, 1997;Grove et al, 1990;Rowe, 1983;Slutske et al, 1997;1\vito & Stewart, 1982), others have not (Lyons et al, 1995; see also Cloninger & Gottesman, 1987;DiLalla & Gottesman, 1989). For example, in two recent twin studies of adult-reported childhood CD (the largest twin studies of CD to date), the estimates of the contribution of genetic factors to variation in risk for CD were 7% (Lyons et al, 1995) versus 43%-71 % .…”
mentioning
confidence: 99%